S-Nitroso-N-acetylcysteine (NAC–SNO) vs. nitrite as an anti-clostridial additive for meat products. Issue 5 (5th February 2021) - Shpaizer, Adi; Kanner, Joseph; Tirosh, Oren
Abstract : NAC–SNO is an efficient preservative against Clostridium spore germination, and under the same conditions and concentrations generates much less methaemoglobin and detectable N -nitrosoamines in the blood, in vivo . Abstract : Nitrite is added to meat products as a preservative and it acts as a bacteriostatic compound against Clostridium botulinum growth. Nitric-oxide (˙NO), myoglobin and S -nitroso-compounds seem to be the main molecules generated from nitrite in meat products, which by decomposition to ˙NO, form the main anti-clostridial factor. The growth of C. sporogenes from activated spores in the presence of 0.5–2.5 mM NAC–SNO was compared to nitrite, both at 37 °C for 5 days and at room temperature for 28 days. The present study demonstrates that NAC–SNO under the same conditions and concentrations, in meat products, acts as an anti-clostridial compound similar to nitrite. In contrast to nitrite which must be activated in meat by heating, NAC–SNO generates the anti-clostridial factor directly, without heating, as was evaluated in an unheated bacteriological medium. The toxic effect of NAC–SNO and nitrite in methaemoglobinaemia and generation of N -nitrosamines in vivo, in mice, were also determined. Mice were gavage fed milk containing 45 mg per kg per bw of nitrite or an equimolar equivalent of NAC–SNO in the presence of 50 mg per kg per bw of N -methylaniline. Nitrite generated methaemoglobinaemia and carcinogenic N -nitrosoamines ( N -nitrosomethylaniline); however, NAC–SNO under the same conditions and concentrations generates much less methaemoglobin and no detectable N -nitrosoamines in the blood, in vivo .